2000
DOI: 10.1023/a:1008977200176
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study compares the reproducibility, construct validity and responsiveness of self-report and parent-report quality of life questionnaires How Are You (HAY) for 8-12-year-old children with asthma. A total of 228 Dutch children with asthma and their parents completed the HAY and daily recorded the child's asthma symptoms in a diary. Additionally 296 age- and -gender matched healthy children and their parents completed the generic part of the HAY. Reproducibility and responsiveness were examined in a sub-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This strong agreement between parents and their chronically ill children has been reported before [19]; however, there are strong arguments that both opinions are of vital importance and should be sought jointly [20]. …”
Section: Discussionsupporting
confidence: 73%
“…This strong agreement between parents and their chronically ill children has been reported before [19]; however, there are strong arguments that both opinions are of vital importance and should be sought jointly [20]. …”
Section: Discussionsupporting
confidence: 73%
“…While parent and teacher reports are important during functional assessments of children with HL, we were most interested in understanding how children perceived their own QOL. Moreover, research has shown that parents are not necessarily accurate reporters of their child's QOL (Le Coq, 2000; Eiser and Morse, 2001; Jovokic, 2004; Goldbeck and Melches, 2005; Cremeens et al, 2006, Uzark et al, 2008). In addition, self-report is considered the standard for assessing perceived HRQOL, and only if a child is too young, too ill, or cognitively unable to answer the questions should parental proxy be substituted (Varni et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the fact that more than half of the target population can not be interviewed directly due to their age, this decision appears to be justified. In addition, studies in which self-assessments of children and assessments by their parents are compared show a high correlation between these two measures [39-41]. …”
Section: Discussionmentioning
confidence: 99%